Histopathological Insights into Granulomatous Lesions: A Comprehensive Study - Archana Kumari; Irbinder K. Bali; Ayushi Chauhan; Falguni Chitkara; Deepika Wadhera (Journal of Pharmacy and Bioallied Sciences)
Background: Granulomatous inflammation is a persistent inflammatory reaction marked by the presence of aggregations of active histiocytes, epithelioid cells, and multinucleate giant cells. This phenomenon is reported in several viral and non-infectious diseases and is classified as a type IV delayed hypersensitivity response. Research Materials and Procedures: The present cross-sectional study was conducted in the histopathology section of the Department of Pathology, MMIMSR, Mullana, from October 2022 to October 2023. A total of 100 cases presenting with granulomatous lesions were analyzed. Detailed clinical data, including age, sex, site of the lesion, and duration of disease, were recorded. Histopathological examination was performed using Hematoxylin and Eosin (H&E) stain, with additional special stains like Ziehl-Neelsen and Periodic Acid-Schiff (PAS) applied where necessary. Materials and Methods: This investigation was conducted at the histology division of the Department of Pathology, MMIMSR, Mullana, between October 2022 and October 2023. The analysis included a total of 100 patients that had granulomatous lesions. Precise clinical information, such as age, gender, location of the lesion, and length of illness, was documented. The histological analysis was conducted using hematoxylin and eosin (H and E) stain, along with supplementary specific stains, such as Ziehl-Neelsen and periodic acid-Schiff (PAS) when needed. Results: Lesions of granulomatous nature were more common in individuals in their third and fourth decades of life, with a little higher occurrence in females (male: female ratio = 1:1.43). The primary location of infection was the gastrointestinal system, accounting for 16% of cases, followed by the urogenital tract at 15% and soft tissues at 13%. Granulomatous pathology-not otherwise specified (GP-NOS) was the most prevalent histological category, representing 52% of cases. It was followed by granulomatous pathology-tubercular (GP-TB) at 15%, granulomatous pathology-leprosy (GP-L) at 3%, and one case of granulomatous pathology-fungal (GP-F). The etiology of 25% of cases was attributed to tuberculosis, whereas in 3% of instances, it was diagnosed as leprosy. The main kind of neoplasms seen were epithelioid cell granulomas, with caseous necrosis being the most prevalent form of necrosis. About 10% of patients had fibrosis, and Langhans giant cells were often documented. Conclusion: Histopathology, with the use of certain stains, continues to be the most reliable method for identifying and classifying granulomatous lesions. Despite the broad use of Bacillus Calmette-Guerin (BCG) vaccine, infections, including tuberculosis (TB), remain the primary cause of granulomatous lesions in our community.